RADIKALISME PELAJAR GENERASI Z: REVISITASI KONTEN DAN METODOLOGI SKI DALAM MATA PELAJARAN PAI - Muhammad Yasser; Pujiyanto Pujiyanto (Alim | Journal of Islamic Education, 2022)
Radicalism among students has reached a very alarming level. This study aims to trace the genealogy of these radicalism viruses that were massive after the 1998 Reformation. After making a selection of various results of field surveys conducted by several credible research institutions, this paper came to a conclusion on the urgency of PAI (Islamic Religious Education) subjects and more specifically SKI (History of Islamic Culture) in fortifying students from various anti-NKRI ideologies labeled with religion. The confusion of religious identity among students, which makes them vulnerable to radicalism, can only be treated by first changing the paradigm of islamic history writing so far that is political-centric and Arab-centric. No less crucial, the role of PAI teachers in recognizing the character of their students who belong to generation Z, in order to find the most effective learning method (inside or outside the classroom). Of course, all these de-radicalization efforts can only be successful with the support of the family and the youth movement, as an educational tripusat.